Character Building Kepemimpinan Lembaga Pendidikan Islam: Analisis Penafsiran Surat Abasa 1-10 - Wahyuni, Sri (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2021)
Surah 'Abasa Verses 1-10 are the verses that contains the formation of the leadership character of the Prophet through the warning ('itab) of Allah to His Prophet. So the research aims to find the character building of the leadership of Islamic educational institutions through the Surah 'Abasa verses 1-10. Using the Tahlili Tafsir Method with the tafsir bir-ra’yi (diroyah), this research results in the concept of character building leadership of Islamic educational institutions through the Surah 'Abasa verses 1-10, among others, the first verse shows the importance of the dimensions of performance and appearance of a leader, the second verse shows the dimensions of social status. The third verse contains an element of the self-esteem dimension, and the fourth verse includes an aspect of the educational dimension, the fifth and sixth verses are aware of their duty to serve the people or their subordinates, the seventh and eighth contain elements of a priority scale dimension, and the two last verses (nine and ten) contain elements of the khauf and raja dimensions, put God first in all activities.ABSTRAKSurat ‘Abasa Ayat 1-10 merupakan ayat-ayat yang berisikan pembentukan karakter kepemimpinan Nabi melalui teguran (‘itab) Allah kepada NabiNya. Maka penelitian bertujuan untuk menemukan character building kepemimpinan lembaga pendidikan Islam melalui Surat ‘Abasa ayat 1-10. Penggunaan Metode Tafsir Tahlili dengan pendekatan tafsir bir-ra’yi (dirayah), maka penelitian ini menghasilkan bahwa konsep character building kepemimpinan lembaga pendidikan Islam melalui Surat ‘Abasa ayat 1-10 antara lain, ayat pertama menunjukkan pentingnya dimensi performa dan penampilan seorang pemimpin, ayat kedua menunjukkan kepada dimensi status sosial, ayat ketiga mengandung unsur dimensi self esteem, ayat keempat mengandung unsur dimensi edukasi, ayat kelima dan keenam menyadari akan tugasnya melayani rakyat atau bawahannya, ayat ketujuh dan kedelapan mengandung unsur dimensi skala prioritas, ayat sembilan dan sepuluh mengandung unsur dimensi khauf dan raja’ atau mengutamakan Allah dalam segala aktivitas